EDUCATIONAL VALUES IN TEXT STORIES RANDAI "MALANGGA SUMPAH" WORKSHOP BUSTAMI GROUP RANDAI BINTANG TAMPALO KENAGARIAN PADANG LAWEH DISTRICT SIJUNJUNG - Syuriadi, Helki; Hasanuddin, Hasanuddin; Manaf, Ngusman Abdul (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2014)
The pourpuse this study were to describe the values of education in Story script of Randai titled â€œMalangga Sumpahâ€ written by Lukman Bustami. The research data was collected by qualitative data, The result of this study is four values of education values in randai script â€Malangga Sumpahâ€ inÂ  by Lukman Bustami there are believe and religious, integrity, caring, and honesty